Social support, self-efficacy and their correlation among patients with type 2 diabetes mellitus: a primary care perspective - Abdul Rashid, Aneesa; Hamzah, Zuhra; Tan, Chai Eng (Malaysian Medical Association, 2018)
Introduction: Social support and self-efficacy are factors that influence patients' health behaviour. However, the relationship between these two factors among patients with Type 2 Diabetes Mellitus (T2DM) has not been adequately explored. This study aims to report social support and self efficacy of Malaysian T2DM patients, and their correlations. Methods: This cross-sectional questionnaire study involved 329 patients with T2DM who received their follow up at a public primary care clinic. Patients were selected via systematic random sampling. Patients self-completed locally adapted versions of the Medical Outcomes Study (MOS) Social Support Survey and Diabetic Management Self Efficacy Scale (DMSES). The scores of both tools were analysed to determine the association and correlation between social support and self-efficacy. Results: The mean score for overall social support was 72.7±21.40 score range (0-100). "Affectionate support" was rated the highest averaged mean score at 78.31±23.71 (score range: 0-100). The mean DMSES score was 147.6±35.5 (score range :0-200), of which "medications" subscale was rated the highest with averaged mean scores 9.07±1.67 (score range: 0-10). Overall social support and self-efficacy were found to be weakly correlated (r=0.197, p<0.001). However, all subscales of social support were moderately correlated with "medications" subscale of self-efficacy. Conclusion: Social support is significantly associated with patients' self-efficacy in handling their own medications.